2008
DOI: 10.1128/cvi.00251-08
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses of Cervids (Cervus elaphus) following ExperimentalMycobacterium bovisInfection and the Implications for Immunodiagnosis

Abstract: Captive and free-ranging wildlife animals are implicated in the maintenance and transmission of bovine tuberculosis and therefore pose a significant obstacle to eradication of the disease from domestic livestock. The current antemortem diagnostic method, the intradermal tuberculin skin test, is impractical for routine use with many wild animals. Antibody-based assays are particularly attractive because the animals are handled only once and immediate processing of the sample is not required. This report charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 47 publications
2
38
1
Order By: Relevance
“…The MAPIA revealed that some of the sera from deer experimentally infected with M. avium subsp. paratuberculosis which produced false-positive responses in the CervidTB STAT-PAK test reacted with MPB83, a key antigen in the specific antibody detection during M. bovis infection (7,9). This unexpected finding is difficult to explain, because the MPB83 protein is not produced by M. avium subsp.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The MAPIA revealed that some of the sera from deer experimentally infected with M. avium subsp. paratuberculosis which produced false-positive responses in the CervidTB STAT-PAK test reacted with MPB83, a key antigen in the specific antibody detection during M. bovis infection (7,9). This unexpected finding is difficult to explain, because the MPB83 protein is not produced by M. avium subsp.…”
Section: Discussionmentioning
confidence: 95%
“…The high number of false-positive responses in the group only vaccinated against Johne's disease (group 4B) at the final bleed is likely to have resulted from the boosting of antibody levels following skin testing with bovine PPD. It is recognized that tuberculin testing can boost antibody responses to certain mycobacterial antigens in M. bovis-infected animals (6,7,19). These results reemphasize the limitations of the currently available vaccines against paratuberculosis when confirmatory serological tests for bovine TB are used following skin testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier work demonstrated that most of alpacas and llamas with TB produced IgG antibodies against the MPB83 protein, irrespective of whether the etiologic agent was M. bovis or M. microti (7,22). This antigen is known to be a major serological target for the immune responses to infections caused by organisms of the M. tuberculosis complex in various host species (13,15,23,40,41). Both RT and the DPP assay include the MPB83 protein in their test antigen composition, which could partly explain the reasonable agreement of the tests with respect to identification of infected animals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have proven the rapid test to be useful in detecting M. bovis infections in llamas (Llama glama), elk (Cervus elaphus), white-tailed deer (Odocoileus virginianus), wild boar (Sus scrofa), Eurasian badgers, brushtail possums (Trichosurus vulpecula), and meerkats (Suricata suricatta); however, validation of the rapid test for domestic cats has yet to be achieved. 6,9,10,12,16,17,26 Multiple antigen print immunoassay identified 16/83, 16 kDa, MPB83, and MBCF as major antigens involved in the humoral immune response in sensitinogen-stimulated cats. Visually all sensitinogen-stimulated cats reacted consistently to antigen MBCF and less consistently to 16/ 83, 16 kDa, and MPB83 antigens (Fig.…”
Section: Introductionmentioning
confidence: 99%